(untitled) (MAUSAM, 1965)
The influence of eddy fluxes of heat at the interface of the oceans and the atmosphere has been numerically estimated in the case of a North Atlantic cyclone: The role placed by such fluxes is discussed; It is shown that the heat sources and sinks associated with tropospheric features at the earth’s surface exert marked influences on the development of mobile pressure systems.